NFκB/Orai1 Facilitates Endoplasmic Reticulum Stress by Oxidative Stress in the Pathogenesis of Non-alcoholic Fatty Liver Disease - Zhang, Bingbing; Li, Ming; Zou, Ying; Guo, Han; Zhang, Bingdong; Xia, Cheng; Zhang, Hongyou; Yang, Wei; Xu, Chuang (Frontiers in Cell and Developmental Biology, 2019)
Non-esterified fatty acids (NEFAs) promote de novo lipogenesis, which resulted in abnormal hepatic lipid accumulation, by NFκB-Orai1 pathway. Oxidative stress and endoplasmic reticulum (ER) stress have been recognized as key mechanisms in non-alcoholic fatty liver disease (NAFLD) pathogenesis. Whether Orai1 facilitates endoplasmic reticulum stress by oxidative stress remains unknown. The rat model of NAFLD was constructed by feeding high-fat diet (HFD). BRL-3A cells were treated NEFAs, Orai1inhibtor BTP2, NFκB inhibitor wogonin or small interfering Orai (siOrai) 1, respected. Content of intracellular reduced glutathione (GSH) and malondialdehyde (MDA), indicating oxidative stress was measured by spectrophotometer. ER stress major proteins PERK, IRE1, ATF6, CHOP and GRP78 were quantified western blot and QRT-PCR analyses. The intracellular location of reactive oxygen species (ROS); Orai1 was measured by western blot and immunofluorescence, cytosolic Ca2+ was measured by flow cytometry. As we expected, the liver of rats with NAFLD were showed lipid droplets in HE and Oil Red O. The descended GSH and increased MDA was found in rats with HFD feed. And ER stress major proteins PERK, IRE1, ATF6, GRP78 and CHOP were significantly increased in HFD groups. In BRL-3A cells, content of GSH was dramatically decreased from 1 h, content of MDA was dramatically increased from 3 h, and expression levels of ER stress were significantly enhanced from 3 h by NEFAs treated. Furthermore, cytosolic Ca2+ was increased from 0.5 h by NEFAs treated in BRL-3A cells. It indicated that NEFAs increased cytosolic Ca2+ to induce oxidative stress, thus ER stress. The content of oxidative stress and ER stress proteins were showed same trends by NEFAs treated in BRL-3A cells. These effects were reversed by the Orai1 inhibitor BTP2 and the NFκB inhibitor wogonin. Moreover, siOrai1 was abrogated NEFAs influence in BRL-3A cells. Last, ROS was found by NEFAs treated in BRL-3A cells, NEFAs treatment enhanced the nuclear localization of NF-κB p65, ORAI1. It was considered that high NEFAs increased cytosolic Ca2+ and enhanced NFκB dependent SOCE and its moiety protein Orai1 to descend GSH, thus induced oxidative stress at earlier stages, furthermore, tempted ER stress in the pathologic progress of NAFLD.